EDWARDS ON THE CHRISTIAN LIFE - Huggins, Jonathan R. (Jonathan Edwards studies, 2014)
This attractive new work by Dane Ortlund is part of a new series by Crossway that aims to draw wisdom from significant voices of the past in living the Christian life. Present volumes in the series include analyses of Calvin, Wesley, Bonhoeffer, Warfield, and Schaeffer, with others to come. Each volume includes a subtitle that is intended to summarize the person’s main. In this case, the subtitle highlights Edwards’s emphasis on the "beauty" of God, which appears as an over-arching theme in Edwards’s writings on many subjects.